2011
DOI: 10.1097/brs.0b013e31820107d0
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Abutment After Direct Vertebral Rotation

Abstract: Six patients with lateral screw direction after a DVR maneuver required screw removal because of proximity to the aorta. All patients had intraoperative confirmation of adequate screw placement before introducing the rod and performing derotation. CONCLUSIONS.: The biologic limitations of vertebrae are approached as we strive to achieve further correction of the spine. Surgeons' experience and methods to assess proper screw placement may give a false sense of adequate final implant position after DVR. Vigilanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 16 publications
1
10
0
1
Order By: Relevance
“…Surprisingly, the torsion index reduction reached 44 %, and the apical vertebral rotation correction averaged 48.3 %, approaching the rates reported in the literature obtained using direct vertebral rotation (DVR) (42.5-64 %) [35][36][37] while obviating potential risks associated with DVR [38]. The unexpectedly high apical vertebral rotational reduction observed in the present patients might be explained by the fact that the corrective maneuver was mediated simultaneously by both rods, preassembled using fixed transverse connectors (Fig.…”
Section: Low Dose Biplanar Stereoradiographysupporting
confidence: 46%
“…Surprisingly, the torsion index reduction reached 44 %, and the apical vertebral rotation correction averaged 48.3 %, approaching the rates reported in the literature obtained using direct vertebral rotation (DVR) (42.5-64 %) [35][36][37] while obviating potential risks associated with DVR [38]. The unexpectedly high apical vertebral rotational reduction observed in the present patients might be explained by the fact that the corrective maneuver was mediated simultaneously by both rods, preassembled using fixed transverse connectors (Fig.…”
Section: Low Dose Biplanar Stereoradiographysupporting
confidence: 46%
“…Essentially, corrective force cannot be exerted on the spinal implant beyond the limit of anchor holding strength during scoliosis surgery. If corrective force reaches the limit of anchor strength, implant breakage or bony fracture reported as “screw plowing” could occur [ 9 ]. According to the results of the present study, averaged pull out and push in force exerted on each screw during SDRRT fell below previously reported safety margin [ 6 ], and therefore this maneuver was demonstrated to be safe for correcting a moderate magnitude curve.…”
Section: Discussionmentioning
confidence: 99%
“…There were many biomechanical studies about holding strength of spinal instruments [ 3 - 6 ]. As regards corrective force exerted on the spinal instruments, several biomechanical models were developed to simulate scoliosis correction in-vitro [ 7 - 9 ]. However, there were only few reports which estimated the actual corrective force during correction maneuver in vivo [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cheng [24] performed a biomechanical analysis of the derotation of the thoracic spine using pedicle screws and found that quadrangularly linked pedicle screws allow for significantly greater torque (with failure at 42.5 Nm±14.5 Nm) compared with a single pedicle screw, bilaterally linked screw, and unilaterally linked pedicle screw constructs. Another advantage is that VCM quadrilateral frame could reduce the possibility that the concave screw may need to be removed because of its proximity to the aorta after the correction by direct vertebral rotation technique [25]. The limitation of this technique is that the success of manipulation of the VCM frame depends on the experience of the surgeon, because too much force could lead to fractures in the periapical region of the vertebrae.…”
Section: Discussionmentioning
confidence: 99%